DYNAMICS OF PANICLE EXSERTION IN RICE: A REVIEW - Khalil, A.I.; Usman, A.; Hamza, T.; Muhammed, A. K. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
Rice yield is a complex trait determined by multiple factors; however, the dynamics of panicle exsertion remain a critical yet frequently overlooked determinant of productivity. This review examines Incomplete Panicle Exsertion (IPE), a phenomenon where the flower head remains partially enclosed in the flag leaf sheath, significantly compromising pollination and seed yield. IPE is a major impediment to production, particularly in Cytoplasmic Male Sterile (CMS) cultivars, where 20–30% panicle enclosure impedes pollination and significantly lowers seed yield. The study outlines the physiological stages of panicle development, from initiation and internode elongation to differentiation, noting that the process is regulated by meristematic activities and hormonal levels. Genetic analysis reveals that, elevated levels of gibberellins (GAs) are advantageous for complete exsertion, while specific genes and Quantitative Trait Loci (QTLs) located on various chromosomes regulate meristem size and elongation. Furthermore, the review discusses the genetic heritability of panicle length, which is influenced by both additive and dominance effects. Finally, the impact of abiotic stresses—including drought, salinity, cold, and iron toxicity—which disrupt metabolic activities and hormonal balance, leading to increased panicle enclosure were analyzed. Ultimately, environmental stress triggers genetic and hormonal changes that resulted in IPE. This review posits that IPE is not merely a structural defect but a morphological indicator of sterility that must be addressed to stabilize yields under unfavorable environmental conditions.